New Sensitive Spectrophotometric Methods for the Determination of Raloxifene Hydrochloride in Pharmaceuticals Using Bromate-Bromide,Methyl Orange and Indigo Carmine - K Basavaiah; U. R. Anil Kumar (E-Journal of Chemistry)
Two new sensitive spectrophotometric methods are proposed for the determination of raloxifene hydrochloride (RLX) using bromate-bromide mixture and two dyes, methyl orange and indigocarmine, as reagents. The methods entail the addition of a known excess of bromate-bromide mixture to RLX in hydrochloric acid medium followed by determination of residual bromine by reacting with a fixed amount of either methyl orange and measuring the absorbance at 520 nm (Method A) or indigo carmine and measuring the absorbance at 610 nm (Method B). In both methods, the amount of bromine reacted corresponds to the amount of RLX. The absorbance is found to increase linearly with concentration of RLX. Under the optimum conditions, RLX could be assayed in the concentration range 0.1-2.0 and 0.5-6.0 μg mL-1 by method A and method B, respectively. The apparent molar absorptivities are calculated to be 1.9×105 and 4.5×104 L mol-1cm-1 for method A and method B, respectively, and the corresponding Sandell sensitivity values are 0.003 and 0.011 μg cm-2. The limits of detection and quantification are also reported for both methods. Intra-day and inter-day precision and accuracy of the developed methods were evaluated as per the current ICH guidelines. The methods were successfully applied to the assay of RLX in its tablet formulation and the results were compared with those of a reference method by calculating the Student’s t-value and F-value. No interference was observed from common tablet adjuvants. The accuracy and reliability of the methods were further ascertained by recovery experiments via standard-addition procedure.